2006
DOI: 10.1007/bf02854892
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis as a tool in local pharmacodynamics

Abstract: A BSTRACTIn many cases the clinical outcome of therapy needs to be determined by the drug concentration in the tissue compartment in which the pharmacological effect occurs rather than in the plasma. Microdialysis is an in vivo technique that allows direct measurement of unbound tissue concentrations and permits monitoring of the biochemical and physiological effects of drugs throughout the body. Microdialysis was fi rst used in pharmacodynamic research to study neurotransmission, and this remains its most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 152 publications
(120 reference statements)
0
10
0
Order By: Relevance
“…Our findings in terms of rapid detection of testosterone in saliva after topical application are also supported by the continuous testosterone increase in the ipsilateral microdialysate of our treated subjects which is based on testosterone skin penetration to skin capillaries and to the subcutaneous interstitial fluid. Although it has been shown that microdialysis is an appropriate method for the investigation of transdermal drug delivery [11,12], we could not find any publication in the relevant literature considering topically applied testosterone. After applying of an accurate dose of the drug on the skin surface, this technique can be used to evaluate drug penetration across the skin for measuring and continuously monitoring drug concentrations in the subcutaneous dialysate.…”
Section: Abdominal Subcutaneous Microdialysis For Topical Testosteronmentioning
confidence: 93%
See 1 more Smart Citation
“…Our findings in terms of rapid detection of testosterone in saliva after topical application are also supported by the continuous testosterone increase in the ipsilateral microdialysate of our treated subjects which is based on testosterone skin penetration to skin capillaries and to the subcutaneous interstitial fluid. Although it has been shown that microdialysis is an appropriate method for the investigation of transdermal drug delivery [11,12], we could not find any publication in the relevant literature considering topically applied testosterone. After applying of an accurate dose of the drug on the skin surface, this technique can be used to evaluate drug penetration across the skin for measuring and continuously monitoring drug concentrations in the subcutaneous dialysate.…”
Section: Abdominal Subcutaneous Microdialysis For Topical Testosteronmentioning
confidence: 93%
“…Microdialysis is a minimal invasive sampling technique that allows continuous measurement of biological molecules, drugs and other substances in the extracellular, interstitial fluid of tissues and organs. Microdialysis can be used to investigate tissue pharmacokinetics, pharmacodynamics, or transdermal delivery of drugs [11,12]. Thus, for example, microdialysis sampling in interstitial subcutaneous tissue can be used for the assessment of percutaneously penetrated testosterone following transdermal administration of testosterone gel.…”
Section: Summary and Conclusion Single Topical Administration Ofmentioning
confidence: 99%
“…The methodology is also useful to assess tissues concentrations of medications in pharmacokinetic investigations [6], [7]. The main limitation of the technique is that recovery from the interstitial space is profoundly affected by molecular size and physicochemical properties of the analyte.…”
Section: Introductionmentioning
confidence: 99%
“…Skin microdialysis is a minimally invasive technique, which has been used successfully during the last 20 years to measure substances in the extracellular space [16,20,24]. Besides this, microdialysis makes it possible to deliver drugs locally into tissues and, at the same time, measure their effects at the site of action [13].…”
Section: Introductionmentioning
confidence: 99%